Parametric synthesis in problems of vector optimization of complex technical systems - Климова, А.С. (Proceedings of National Aviation University (archive), 2009)
The article is considered a methodology to specify the main characteristics of compound technical system. The methodology is used on the initial stages of an aerospace system design.